Business Communication Strategy of Egg White MSMEs in Building Consumer Trust and Attractiveness - Muhammad Albi Putra Pratama; Rio Kurniawan; Mochammad Sakti Aditya Pratama (Yayasan Citra Dharma Cindekia, 2026)
The development of MSMEs in the health-based processed food sector, such as egg white products, continues to grow alongside the trend of healthy lifestyles. However, these products are often perceived as simple commodities lacking market differentiation. This study aims to analyze integrated business communication strategies implemented by egg white MSMEs to enhance consumer trust and product appeal. A qualitative descriptive approach was employed. Data were gathered through in-depth interviews with 3 egg white MSME owners and 15 regular consumers, field observations of marketing channels, and structural documentation. Data analysis followed the Miles and Huberman framework, comprising data reduction, data display, and conclusion drawing. The conceptual and empirical findings indicate that an Integrated Marketing Communication (IMC) strategy combining clear nutritional education, service excellence, operational transparency, and clean visual branding significantly shapes positive consumer perceptions. Transparent and honest communication reduces perceived risk and establishes consumer trust, while aesthetic packaging design acts as a primary stimulus driving emotional attachment and purchase intention.